Immediate Perinatal Outcome of Neonates with Maternal Hypertensive Disorders in Pregnancy - Hassan, Mahmuda; Choudhury, Ferdousi; Begum, Marium; Rahman, Hamidur; Akhter, Sayeba (Journal of Nepal Paediatric Society, 2013)
Introduction: Hypertensive disorders of pregnancy seem to be one of the major causes of maternal morbidity and mortality leading to 10-15% of maternal deaths especially in the developing world. This study examines the perinatal outcome of neonates with mothers having hypertensive disorder of pregnancy. Materials and Methods: Seventy three mothers and their newborn babies were selected. Mothers with Gestational hypertension, preeclampsia, eclampsia, chronic hypertension, preeclampsia superimposed on chronic hypertension were included. Gestational diabetics (GDM), chronic maternal diseases, infant of diabetic mother (IDM), babies with major congenital malformations were excluded. Results: Thirty five mothers (47.9%) had regular antenatal check up (ANC) and 38 (52%) had irregular. Nineteen mothers (26%) were primipara and 54 (74%) were multipara. Forty four mothers (60%) had positive family history or had own history of hypertensive disorder during their previous pregnancy. 13 mothers (17.8%) had normal vaginal delivery (NVD), 60 mothers (82.19%) had lower uterine cesarean section (LUCS). 30 babies (41%) were admitted. 44 mothers (60%) had gestational hypertension, 21 had (28.6%) pre-eclamtic toxemia (PET), 3 had (4.1%) eclampsia, 5 had (6.8%) essential hypertension 3 of them subsequently developed PET. Mean maternal age 26.86 years, gestational age 34.15 (±1.46)weeks among admitted and 36.30 (±1.6)weeks among non-admitted group. Mean birth weight was 1.69 (±0.39) kg. among admitted and 2.71 (±0.31) kg. in non-admitted babies. Seven pregnancies (9.58%) were twin, macerated 1 twin among was among 2 pregnancies (2.7%), 5 intra uterine death (IUD) observed in single pregnancy. Conclusion: Significant number of babies with maternal hypertensive disorder of pregnancy needed hospitalization, mean birth weight and gestational age was less than that of the non-admitted group. DOI: http://dx.doi.org/10.3126/jnps.v33i3.9252 J. Nepal Paediatr. Soc. 2013;33(3):190-195